2011
DOI: 10.1021/ma201585v
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity Decrease and Reinforcement in Polymer–Silsesquioxane Composites

Abstract: The rheological behavior of poly(ethylene-alt-propylene) (PEP), polydimethylsiloxane (PDMS) and polyisoprene (PI, two molecular weights: 70k and 200k) melts containing polyhedral oligomeric silsesquioxane (POSS) molecules was investigated by means of small angle scattering (SAXS and SANS) and oscillatory shear rheology. The dependence of the nanocomposite viscosity on the polymer–particle solubility and polymer molecular weight was studied. At high filler fractions all polymers exhibited hydrodynamic reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
105
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 50 publications
6
105
0
Order By: Relevance
“…In their seminal 1975 study, Malinskii and co-workers1112 reported that addition of small amounts of unfunctionalized particulate fillers to high molar mass polymers produce an unexpected decrease in viscosity, followed by an increase at higher filler contents. These findings have since been extended to a variety of PNCs on the basis of unfunctionalized as well as polymer-functionalized NPs, including polystyrene13, magnetite14 and fullerene1415 nanoparticles in polystyrene hosts, silsesquioxane–polymer composites161718, and tethered silica–polymer composites19. The most recent studies have also established empirical NP and polymer size requirements to achieve the viscosity reductions, which have been investigated in detail by simulations20 and theory2122; however, how and why NPs violate the Einstein–Batchelor viscosity law in polymers remains a puzzle.…”
mentioning
confidence: 88%
“…In their seminal 1975 study, Malinskii and co-workers1112 reported that addition of small amounts of unfunctionalized particulate fillers to high molar mass polymers produce an unexpected decrease in viscosity, followed by an increase at higher filler contents. These findings have since been extended to a variety of PNCs on the basis of unfunctionalized as well as polymer-functionalized NPs, including polystyrene13, magnetite14 and fullerene1415 nanoparticles in polystyrene hosts, silsesquioxane–polymer composites161718, and tethered silica–polymer composites19. The most recent studies have also established empirical NP and polymer size requirements to achieve the viscosity reductions, which have been investigated in detail by simulations20 and theory2122; however, how and why NPs violate the Einstein–Batchelor viscosity law in polymers remains a puzzle.…”
mentioning
confidence: 88%
“…Nanocomposites containing nanoparticles have been investigated experimentally such as systems of POSS nanoparticles (R = 1 nm) dispersed in poly(ethylene-alt-propylene) matrix 27 or cadmium selenide nanoparticles dispersed in PS matrix 66 . While in other theoretical studies 70,85,[97][98][99] only the dilute nanoparticle loading has been explored, we investigate for the first time, the nanoparticle diffusion for a wide nanoparticle concentration range.…”
Section: B Nanoparticle Diffusionmentioning
confidence: 99%
“…However, in the case of small nanoparticles dispersed in polymer melts 27,79,102,103 and solutions 104,105 , the validity of Equation 4 is questionable as observed by experiments 66 and theory 69,106 . The nanoparticle diffusivities of the simulated nanocomposite systems are calculated from the mean square displacement measurements given by:…”
Section: B Nanoparticle Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their extraordinary and improved mechanical properties, this new class of materials has recently received tremendous attention in both scientific and industrial communities. It is shown that adding nanoparticles to polymer melts [4][5][6][7][8][9][10][11][12] can lead to an increase or a decrease in the viscosity, depending on such conditions as filler concentration, filler size, chain length, and polymerparticle interactions. For example, the viscosity of polymer melt decreases by adding nanoparticles with sizes smaller than polymer chain length scales (radius of gyration).…”
Section: Introductionmentioning
confidence: 99%